2006
DOI: 10.1016/j.amjcard.2005.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Angiographic Analysis With a Cobalt Alloy Coronary Stent (Driver) in Stable and Unstable Angina Pectoris

Abstract: The Clinical and Angiographic analysis with a Cobalt Alloy Coronary Stent (Driver) (CLASS) study was a prospective, nonrandomized, multicenter study designed to assess the safety and efficacy of a cobalt-chromium alloy-based stent in patients with stable or unstable angina pectoris. A total of 203 lesions were treated in 202 enrolled patients. The percentage of major adverse cardiac event-free patients was 87.6% (177 of 202) at 6 months (primary safety end point; major adverse cardiac events were defined as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
3
15
0
4
Order By: Relevance
“…Also, several clinical studies using thin-strut bare-metal cobalt-chromium stents have shown the advantages of enhanced visibility, deliverability and radial strength, and reducing restenosis when compared with bare-metal stainless steel stents [2427]. In this context, the Supraflex SES was developed using the same proven biodegradable polymer-based, sirolimus-eluting technology as on the Supralimus-Core SES but was applied to the thinner struts (60  μ m) cobalt-chromium stent platform (Flexinnium bare-metal stent).…”
Section: Discussionmentioning
confidence: 99%
“…Also, several clinical studies using thin-strut bare-metal cobalt-chromium stents have shown the advantages of enhanced visibility, deliverability and radial strength, and reducing restenosis when compared with bare-metal stainless steel stents [2427]. In this context, the Supraflex SES was developed using the same proven biodegradable polymer-based, sirolimus-eluting technology as on the Supralimus-Core SES but was applied to the thinner struts (60  μ m) cobalt-chromium stent platform (Flexinnium bare-metal stent).…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of OMEGA study was to evaluate safety and efficacy of the REBEL Stent and to compare it with other contemporary BMS such as Vision, Driver, Liberte and Tsunami. Availability of published data and absence of any relevant differences in coronary risk factors and cardiac history between the OMEGA study and previous trials with those stents allow us to compare patient and lesion characteristics and outcome data [13][14][15][16][17][18]. Despite the fact that definitions of TVF or its individual components was not Bi-segment™ inner lumen catheter to provide outstanding flexibility and pushability…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] As taxas do desfecho primário ECAM foram semelhantes em ambos os grupos, bem como os desfechos de óbito, IAM e RVA isoladamente. Além disso, foi demonstrado que o stent de cromo-cobalto apresentou maior taxa de implante direto, ou seja, menor necessidade de pré-dilatação das lesões.…”
Section: Discussionunclassified
“…[11][12][13][14]16,17 A redução da espessura das hastes também possibilita stents mais flexíveis, com menor perfil de cruzamento e com evidências clínicas de menor proliferação neointimal em relação ao aço em algumas casuísticas. 9,12,14,16 Entre as ligas metálicas atuais destacam-se a de cromo-cobalto e a de platina-cromo.…”
Section: Discussionunclassified